Self-assembled amphiphilic DNA-cholesterol/DNA-peptide hybrid duplexes with liposome-like structure for doxorubicin delivery - Choi, Kyung-mi; Kwon, Ick Chan; Ahn, Hyung Jun (ELSEVIER SCI LTD, 2013)
DNA nanoparticles have been proposed for drug encapsulation and intracellular delivery, but it has remained a challenge to rationally design DNA nanoparticles for delivery of drug to human cancer cells, not to normal cells. In this study, we synthesized an amphiphilic DNA hybrid duplex by using Watson-Crick base pairing and DNA bioconjugation with cholesterol or tLyp-1 tumor-homing peptide. The resulting amphiphilic DNA hybrid duplexes can self-assemble in an aqueous solution into liposome-like nanoparticles (c-DNA-p nanoparticles) with the exposure of tLyp-1 peptides to their outside. As a nanocarrier for doxorubicin, c-DNA-p nanoparticles can efficiently intercalate doxorubicin and also show the pH-dependent complexing/dissociation behaviors with doxorubicin, resulting in release of doxorubicin into cytosol after cell uptake. Moreover, tLyp-1 peptides with cell penetrating properties and specific binding ability for Neuropilin-1 receptors enable doxorubicin-loaded c-DNA-p nanoparticles to be delivered into the target cells through the NRP-1-dependent internalization pathway. Here, we demonstrated the targeted delivery of doxorubicin to MDA-MB231 breast cancer cells, compared to HFF normal cells. These results provide an alternative approach to specifically delivering doxorubicin into targeted cells for cancer therapy as well as controlling drug release under the acidic conditions such as endosomes or lysosomes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: NANOPARTICLES; CYTOTOXICITY; CANCER